PROMOSI PERPUSTAKAAN UMUM KOTA PADANG - Fitria, Doris (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
This study describes the Promotion of Padang City Public Library. This activity can inform the promotion has been carried out, to the extent to which the development and creativity of the promotion carried out as well as techniques and breakthroughs in solving problems faced by the "Padang City Public" library. This study used a descriptive qualitative approach. The data collected by interviews, this in itself obtained directly the technicalities and tips from the promotion of the Padang City Public Library. The impact of this study explains that the techniques carried out through the Mobile Library Service by using the Read Aloud method and story telling using the muppet doll tone, book review, Care Free Day, Speech Competition, conducting library development activities both specifically and to vertical institutions. With regard to it promotion through technology. Meanwhile, social media promotion of the Padang City Public Library used includes Face Book, Whatshap, Instgram, Youtube and through the Librarian Working Group through book donations. The success of this promotion has a significant impact on continuing to increase the number of library visits every month. Overcome the obstacles of this promotion, the library also provides opportunities, space and opportunities to visitors in the form of filling out surveys to meet the needs of users of the required collections.